2021
DOI: 10.3390/antiox10071015
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Nano-Curcumin Supplementation on Risk Factors for Cardiovascular Disease: A GRADE-Assessed Systematic Review and Meta-Analysis of Clinical Trials

Abstract: Background: Previous studies have indicated that curcumin supplementation may be beneficial for cardiometabolic health; however, current evidence regarding the effects of its nanorange formulations, popularly known as “nano-curcumin”, remains unclear. This systematic review and meta-analysis aimed to determine the impact of nano-curcumin supplementation on risk factors for cardiovascular disease. Methods: PubMed, Scopus, Embase, and ISI web of science were systematically searched up to May 2021 using relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 85 publications
2
55
1
Order By: Relevance
“…The effect of curcumin supplementation on BP is not fully conclusive. Damoon et al reported that the hypotensive effect of nanocurcumin on cardiovascular disease is mainly focused on decreasing SBP [ 42 ]. Amir et al observed favourable effects of curcumin administration only on SBP levels in different participants with a ≥12-week follow-up [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of curcumin supplementation on BP is not fully conclusive. Damoon et al reported that the hypotensive effect of nanocurcumin on cardiovascular disease is mainly focused on decreasing SBP [ 42 ]. Amir et al observed favourable effects of curcumin administration only on SBP levels in different participants with a ≥12-week follow-up [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Piperine, the active component of black pepper, can increase the bioavailability of curcumin when piperine and curcumin are co-ingested [ 30 ]. Microparticulation and surface treatment techniques have also been shown to enhance the bioavailability of curcumin [ 31 , 32 ]. Previous paralleled and crossover design studies that examined the effect of curcumin on EIMD and DOMS markers are summarized below ( Table 1 ).…”
Section: Curcuminmentioning
confidence: 99%
“…In contrast to numerous animal studies that showed a decrease in myeloperoxidase activity after curcumin administration ( 214 – 216 ), an unexpected increase was observed in the human study ( 213 ). A recently published systematic review on the effect of nano-curcumin supplementation revealed an overall increase in HDL-C levels ( 217 ). Encapsulation of curcumin in nanoformulations has been shown to prolong circulation time and increase its bioavailability and solubility in several in vitro studies ( 218 221 ) and already has been used in some clinical trials ( 222 225 ).…”
Section: Impact Of Dietary Intake Of Polyphenols On Hdl Functionmentioning
confidence: 99%